Perbandingan Penginputan Transaksi Secara Manual Menggunakan Accurate pada Laporan Keuangan Input Transaksi Manual dengan Accurate di Laporan Keuangan - Meytha, Sri; Delfin. M, Vallen Ocshelyn (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This abstract discusses the comparison between manually inputting transactions using Accurate in financial reports. The manual transaction input method involves the process of manually entering data into the accounting system, such as recording purchase, sales and other expenditure transactions. Although this method can produce accurate financial reports, it requires more time and effort from the party doing the inputting. Apart from that, the risk of errors is also higher because data entry is done manually.On the other hand, using Accurate as a transaction input system can increase the efficiency and accuracy of financial reports. Accurate is an accounting software designed to help entrepreneurs or accountants in managing company financial transactions. By using Accurate, transaction input can be done automatically through integration with various data sources, such as the cashier system, purchasing system and sales system. This reduces the need to enter data manually, so the time and effort required can be minimized.Apart from that, Accurate is also equipped with an automatic validation feature which can reduce the risk of human error in inputting transactions. This feature will check the data entered and provide warnings or notifications if there are errors or discrepancies with applicable accounting rules. Thus, the accuracy of financial reports can be improved.In this research, a comparison will be made between manually inputting transactions and using Accurate in financial reports. By comparing these two methods, it is hoped that information can be found that can help entrepreneurs or accountants in choosing the most efficient and accurate transaction input method for their company.